PERCEIVED RISK AND MOBILE SHOPPING: DO THEY MATTER? - Sok Bee- Tang; Ahmad Zainal Abidin Abd Razak (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2023)
This paper examines the relationship between six perceived risk factors and online mobile shopping behaviour among youths in Malaysia. Specifically, this study will examine the relationship between product performance risk, health risk, time risk, financial risk, security risk and social risk towards mobile shopping behaviour. This survey is based on a judgement sampling method and data collection was done using an online survey method in a local private university and the hypotheses were tested using quantitative analysis. The online survey involved a total of 383 respondents and data were processed via IBM SPSS Statistics 24 and AMOS 22. The findings revealed four perceived risk factors (product performance risk, time risk, financial risk, security risk) are significantly affecting mobile shopping behaviour while two factors (health risk and social risk) are insignificant. This study offers valuable insights to online retailers, enabling them to develop strategies that mitigate risks in the mobile shopping environment, particularly focusing on financial risk. Additionally, the study presents perspectives on various dimensions of perceived risk that hold significance for youths. These insights can prove instrumental in enhancing stakeholder engagement and facilitating the creation of effective policies and strategies for the mutual benefit of consumers and online retailers in the future.